Biosorption of dye using food processing-derive Rhizopus oligosporus - Muhammad Alif Abas (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
High dye content in the waste water from industry mainly textile industry became an issue in the environment. The dye compound used in this project was Methylene Blue. The fungal which is Rhizopus oligosporus was growh in solid state fermentation The fungal biosorbent was characterized by Scanning Electron Microscopy (SEM) technique. The objective of this project is to evaluate the effect of the removal of dyes from aqueous solution using fungi as biosorption. Effect of physicochemical factors such as the quantity of adsorbent dose, pH and time are evaluated and optimized in this study with the most optimal data obtained is 0.70 g, pH 6.5 and 3 hours 42 minutes of use, each with 82.00% percentage of dye removal. All the concentration of the solution was analyzed by using UV-Vis Spectrophotometer. Based on the results generated, the fungus Rhizopus oligosporus emerged as superior biosorption to remove coloring compounds from aqueous solutions with a high adsorption capacity and low-cost process.